Numerical investigation of the hydrogen swirl combustion flow in a micro gas turbine burner. (December 2022) - Liu, Hong; Zeng, Zhuoxiong; Guo, Kaifang
The influence of swirl angle and hydrogen mixing ratio on the performance of micro gas turbine combustor is discussed by numerical simulation based on computational fluid dynamics (CFD) method, the parameters such as combustion characteristics and pollutant emissions are analyzed. The realizable k-epsilon model is adopted for turbulence simulation, the combustion model is general finite rate model. The results indicated that increasing swirl number reduces the temperature and NO emission. As hydrogen content in the fuel increases, flame length is slightly shortened, temperature in the combustion chamber rises, and temperature distribution becomes more uniform, NO emission at central axis becomes highly, while CO2 and CO emissions decrease. When hydrogen mixing ratio is 50%, the maximum NO emission is about 3 times that of pure methane combustion, and CO2 mass fraction is reduced by 43.9%, moreover, outlet CO emission is reduced by nearly 70%. The hydrogen mixing ratio has a greater impact on pollutant emissions, the sensitivity level of NO and CO emissions to hydrogen mixing ratio reaches 0.25 and 0.39 respectively. As hydrogen mixing ratio and swirl number increases, pressure loss grows, and average turbulent kinetic energy on central plane gradually rises, mainly in outlet region and recirculation zone. Increasing swirl number makes the synergy better, but hydrogen mixing has little effect on the synergy distribution.